Enterprise Risk Management, Capital Structure, Financial Performance, and Firm Value - Hijroini Fajaryati; Ridwan Nurazi; Rini Andriani; Fadli (YAYASAN BINA BISNIS NUSANTARA MEDAN, 2026)
This study analyzes the influence of Enterprise Risk Management (ERM) on capital structure, financial performance, and firm value in banking companies listed on the Indonesia Stock Exchange during 2017–2024. Using a quantitative approach, this study employs secondary data from annual reports, financial statements, IDX publications, OJK reports, and Bank Indonesia reports. Data were analyzed using Generalized Structured Component Analysis (GSCA) to test direct, indirect, and mediating effects. ERM is measured using a COSO-based disclosure index, capital structure is measured by DER and DAR, financial performance by ROA, ROE, and NIM, and firm value by Tobin’s Q. The results show that ERM has a positive and significant effect on capital structure, financial performance, and firm value. Capital structure negatively affects firm value, while financial performance does not significantly affect firm value. These findings indicate that ERM functions as a strategic value driver that strengthens risk governance, capital planning, and market confidence in Indonesian banking.